Graham-Little Piccardi Lassueur Syndrome: case report Síndrome de Graham-Little Piccardi Lassueur: relato de caso - Raquel Bissacotti Steglich; Renata Elise Tonoli; Giselle Martins Pinto; Fernanda Melo Müller; Isabelle Maffei Guarenti; Ernani Siegmann Duvelius (Sociedade Brasileira de Dermatologia, 2012)
A 33-year-old woman presented with a 3-year history of progressive alopecia of the scalp. Past treatment with hydroxicloroquine did not show improvement. Physical examination revealed multiple areas of alopecia with atrophic aspect of the scalp, and axillary and pubic hypotrichosis. Dermoscopy showed hyperkeratosis and accentuation of follicular ostia. Anatomopathological examination revealed decrease in the number of hair follicles, upper perifollicular infiltrate and areas with fibrosis. The Piccardi-Lassueur-Graham-Little syndrome is a rare disorder, characterized by the triad of multifocal scarring alopecia of the scalp, keratotic follicular eruption and hypotrichosis of axillary and pubic regions. Management is a challenge and many medications tried have controversial results. We report a case of this rare syndrome which improved with corticoids. Mulher, 33 anos, apresenta quadro de alopecia progressiva do couro cabeludo há 3 anos. Tratamento com hidroxicloroquina há 12 meses, sem apresentar melhora. Ao exame físico exibe múltiplas áreas de alopecia cicatricial no couro cabeludo, além de hipotricose axilar e pubiana. A dermatoscopia evidencia hipercetose folicular e acentuação dos óstios foliculares. O exame anatomopatológico revela diminuição do número de folículos pilosos, infiltrado perifolicular e fibrose. A síndrome de Graham-Little Piccardi Lassueur é uma dermatose rara, caracterizada pela tríade de alopecia cicatricial multifocal do couro cabeludo, ceratose folicular disseminada e hipotricose das regiões axilares e pubianas. A terapêutica desta dermatose é um desafio, muitas medicações relatadas tem resultados controversos. Relatamos o caso desta síndrome rara que apresentou melhora com corticoterapia.